Leadership in Action : Issues and Observations - Five Myths About Executive Coaching - Riddle, Douglas; Zan, Lindsey; Kuzmycz, Daniel (Center for Creative Leadership, 2009)
Today's organizational world is experiencing a rush of its own kind: the rush to use the powerful intervention of coaching. Coaching is booming, and the overwhelming perception is that it is doing so with success. However, in the absence of universal standards and credentials, the selection and engagement of coaches has been fraught with confusion, anxiety, and unhappiness.